Information technology and the location of computer services : location of data entry and processing services. - HOWLAND, Marie (1995)
Examines the reasons why some computer services are conducted offshore, and the characteristics of such services. Identifies which jurisdication in the industrialized countries, central cities, suburbs or rural areas compete most directly with offshore sites.